Komitmen pegawai sebagai mediasi pengaruh karakteristik individu terhadap kinerja pegawai - Gunawan, Ketut (Jurnal Ilmu Manajemen, 2023)
This research aims to investigate the influence of individual characteristics on employee performance and the role of employee commitment as a mediator in the relationship between individual characteristics and employee performance. The research was conducted in the Badan Usaha Milik Daerah (BUMD) of Buleleng Regency, including the Regional Water Company and the Regional Market Company. A total of 80 employees participated in this study. A quantitative approach, through path analysis, was used in this research. The research results indicate a significant influence of individual characteristics on employee commitment: individual characteristics significantly affect employee performance, employee commitment significantly affects employee performance, and employee commitment can mediate the influence of individual characteristics on employee performance. Discussions regarding key points in employee commitment can be adopted as stimuli to improve individual characteristics and employee performance in both BUMDs in the Buleleng Regency.